Unprofitable horizontal mergers, external effects, and welfare - Oliver Budzinski; Jürgen-Peter Kretschmer (Technische Universität Ilmenau, Institut für Volkswirtschaftslehre, 2015)
Standard analysis of mergers in oligopolies along the lines of the popular Farrell-Shapiro-Framework (FSF) relies regarding its policy conclusions sensitively on the assumption that rational agents will only propose privately profitable mergers. If this assumption held, a positive external effect of a proposed merger would represent a sufficient condition to allow the merger. However, the empirical picture on mergers and acquisitions reveals a significant share of unprofitable mergers and economic theory, moreover, demonstrates that privately unprofitable mergers can be the result of rational action. Therefore, we drop this restrictive assumption and allow for unprofitable mergers to occur. This exerts a considerable impact on merger policy conclusions: while several insights of the original analysis are corroborated (f.i. efficiency defence), a positive external effect does not represent a sufficient condition for the allowance of a merger anymore. Applying such a rule would cause a considerable amount of false decisions.
Keywords: L13; L41; K21; D43; 330; mergers & acquisitions; oligopoly theory; horizontal merger policy; profitability of mergers; antitrust